FORMATION OF COGNITIVE ACTIVITY IN PRESCHOOL CHILDREN - Kamoliddin KHUSHBOKOV (Scholar Express Journal, 2023)
This article is written about the formation of cognitive activity in preschool children. By the beginning of early childhood, the first operations of thinking occur in a child. We can see this in the fact that after he is able to try to pick up an object, he studies it carefully.
Keywords: child; cognition; activity; period